2020
DOI: 10.3389/fnhum.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

Neuroergonomic Assessment of Hot Beverage Preparation and Consumption: An EEG and EDA Study

Abstract: Neuroergonomics is an emerging field that investigates the human brain about behavioral performance in natural environments and everyday settings. This study investigated the body and brain activity correlates of a typical daily activity, hot beverage preparation, and consumption in a realistic office environment where participants performed natural daily tasks. Using wearable, battery operated and wireless Electroencephalogram (EEG) and Electrodermal activity (EDA) sensors, neural and physiological responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 80 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…In addition, the private label compared to major brand also showed higher approach in the visual and tactile exploration phases. Similarly, Sargent et al (2020) compared two machines to prepare hot beverages, one from a market leader and the other from a follower machine in an office setting (n = 26). It was shown that the market leader machine's user interface was preferred, indicated by self-reports and supported by significant valence measured by frontal alpha asymmetry and arousal extracted from electrodermal activity measures.…”
Section: Real Cues (N = 11)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the private label compared to major brand also showed higher approach in the visual and tactile exploration phases. Similarly, Sargent et al (2020) compared two machines to prepare hot beverages, one from a market leader and the other from a follower machine in an office setting (n = 26). It was shown that the market leader machine's user interface was preferred, indicated by self-reports and supported by significant valence measured by frontal alpha asymmetry and arousal extracted from electrodermal activity measures.…”
Section: Real Cues (N = 11)mentioning
confidence: 99%
“…Sargent et al (2020) Two machines to prepare hot beverage. 26 participants (14 females) ++Brouwer et al (2017) Cooking and tasting chicken or mealworms stir-fry dishes.41 participants (19 female) ++ + Olszewska-Guizzo et al (2020) Six landscape scenes (urban green and urban downtown).…”
mentioning
confidence: 99%
“…Beside these basic cognitive aspects of work, another group of studies addressed the question of user experience in cognitive neuroergonomics. They deal with economic decisions or more generally with consumer behavior ( Khushaba et al, 2013 ; Muñoz et al., 2019 ; Roberts et al, 2018 ), user interaction ( Sargent et al, 2020 ), or user satisfaction ( Keum et al, 2018 ). On a more macroscopic level, several studies dealt with spatial cognition and sensation in real-life situations in urban environments ( Al-Barrak et al, 2017 ; Djebbara et al, 2019 ; Mavros et al, 2016 ) or while walking through an art museum ( Cruz-Garza et al, 2017 ).…”
Section: Going Mobilementioning
confidence: 99%
“…Beside these basic cognitive aspects of work, another group of studies addressed the question of user experience in cognitive neuroergonomics. They deal with economic decisions or more generally with consumer behavior (Khushaba et al, 2013;Munoz, Gallego, Salazar, & Rodriguez, 2019;Roberts et al, 2018), user interaction (Sargent, Watson, Ye, Suri, & Ayaz, 2020) or user satisfaction (Keum, Lee, Lee, & In, 2018). On a more macroscopic level, several studies dealt with spatial cognition and sensation in real life situations in urban environments (Al-Barrak, Kanjo, & Younis, 2017;Djebbara, Fich, Petrini, & Gramann, 2019;Mavros, Austwick, & Smith, 2016) or while walking through an art museum (Cruz-Garza et al, 2017).…”
Section: State Of the Artmentioning
confidence: 99%
“…This is crucial for situations that could entail hazardous results in case a system user is not able to respond to situational requirements due to maladjusted states of arousal or affect, as for example during driving (Thirunavukkarasu, Abdi, & Mohajer, 2016). It is also possible to improve usability evaluations using EEG emotion classification during the interaction with everyday utensils (Sargent et al, 2020).…”
Section: Hands-on Neuroergonomicsmentioning
confidence: 99%